Summer forage crops - NSW Agriculture (Sydney, N.S.W. : NSW Agriculture, 2002)
"Farm business and trade: Farm budgets and costs: Livestock gross margins" -- web page.
Dryland forage sorghum -- irrigated hybrid forage sorghum -- irrigated forage (hybrid) millet -- spray irrigated maize for silage.
Title from title screen (viewed August 5, 2003).
Mode of access: World Wide Web. Available at: http://www.agric.nsw.gov.au/reader/872
System requirements: Acrobat Reader to view/print PDF files.
Selected for archiving
Keywords: Agriculture -- Murrumbidgee River Region (N.S.W.) -- Periodicals; Agriculture -- New South Wales -- Economic aspects -- Periodicals; Crops -- New South Wales -- Periodicals; Farm management -- Data processing -- New South Wales -- Periodicals